Development of a Reproducible Model of Parenteral Nutrition-Associated Liver Disease in Rats - Whitehead, Alia; Schwartz, Marshall Z. (European Journal of Pediatric Surgery, 2016)
Purpose For patients with intestinal failure, parenteral nutrition (PN) is a life-saving therapy. Unfortunately, hepatic dysfunction will occur in 40 to 60% of children on long-term PN. While the hepatic dysfunction is likely multifactorial, one important chemical component of the disease may be aluminum contamination of the PN. Previous studies have shown a reduction in liver injury by decreasing the aluminum concentration in PN in a pig model. We sought to develop a rat model of PN-associated liver disease (PNALD) with parenteral aluminum.Methods Adult Sprague–Dawley rats had intravenous long-term catheters placed. The control group underwent daily injections of saline. The study rats had daily injections of either 2 or 3 mg/kg aluminum chloride (AlCl3). At the end of 4 weeks, the rats were euthanized and liver and blood samples were taken. The livers were analyzed and graded by a pathologist for histological evidence of liver degeneration and acute and chronic inflammation. The serum was analyzed for total bilirubin, alkaline phosphatase, alanine aminotransferase (ALT), and aspartate aminotransferase (AST).Results There was no difference in serum values of total bilirubin, alkaline phosphatase, ALT, or AST. There was no difference in acute inflammation among the groups (1 [control], 1.2 [2 mg/kg], 1.1 [3 mg/kg]). The rats treated with parenteral aluminum had significantly more Kupffer cells than the control group (0.1 [control], 3 [2 mg/kg], 2.2 [3 mg/kg], p < 0.0001 [control vs. 2 mg/kg] and 0.0032 [control vs. 3 mg/kg]). There was also more liver degeneration in the parenteral aluminum groups than the control group (1 [control], 2 [2 mg/kg], 2.5 [3 mg/kg], p = 0.0341 [control vs. 2 mg/kg] and 0.009 [control vs. 3 mg/kg]). However, there was no difference between 2 and 3 mg/kg AlCl3 for either variable.Conclusion This study suggests that 4 weeks of parenteral aluminum can induce chronic inflammation and degeneration of the liver in rats. Therefore, we believe that daily injections of parenteral aluminum can produce a viable model of PNALD in rats. However, further studies are warranted, including measurement of serum aluminum levels in infants on PN.
Keywords: parenteral nutrition; cholestatic liver disease; rat